Sintering of magnesium oxide in presence of liquid phase - Chakrabarti S.; Agrawal G.N.; Narasimhan M.D. (My University, 2025)
An intimate mixture of tri-component eutectic with 23.0% CaO, 15.0% Al2O3and 62.0% SiO2was prepared at 1400°C for 2 hours. Effects of eutectic mixture (3 and S wt %) on the sintering of magnesia was studied at various temperatures (1250°-1450°C) and times (up to 100 minutes). More than 97.0% of theoretical density was achieved by magnesia compacts containing 5% eutectic mixture at 1450°C. Microstructures of magnesium oxide with additive showed rounded periclase crystals. © 1981 Taylor & Francis Group, LLC.